Dopaminergic and Metabolic Correlations With Cognitive Domains in Non-demented Parkinson’s Disease - Han, Linlin; Lu, Jiaying; Tang, Yilin; Fan, Yun; Chen, Qisi; Li, Ling; Liu, Fengtao; Wang, Jian; Zuo, Chuantao; Zhao, Jue (Frontiers in Aging Neuroscience, 2021)
Background: Accruing positron emission tomography (PET) studies have suggested that dopaminergic functioning and metabolic changes are correlated with cognitive dysfunction in Parkinson’s disease (PD). Yet, the relationship between dopaminergic or cerebral metabolism and different cognitive domains in PD is poorly understood. To address this scarcity, we aimed to investigate the interactions among dopaminergic bindings, metabolic network changes, and the cognitive domains in PD patients. Methods: We recruited 41 PD patients, including PD patients with no cognitive impairment (PD-NC; n = 21) and those with mild cognitive impairment (PD-MCI; n = 20). All patients underwent clinical evaluations and a schedule of neuropsychological tests and underwent both 11C-N-2-carbomethoxy-3-(4-fluorophenyl)-tropane (11C-CFT) and 18F-fluorodeoxyglucose (18F-FDG) PET imaging. Results: 11C-CFT imaging revealed a significant positive correlation between executive function and striatal dopamine transporter (DAT) binding at both the voxel and regional levels. Metabolic imaging revealed that executive function correlated with 18F-FDG uptake, mainly in inferior frontal gyrus, putamen and insula. Further analysis indicated that striatal DAT binding correlated strictly with metabolic activity in the temporal gyrus, medial frontal gyrus and cingulate gyrus. Conclusion: Our findings might promote the understanding of the neurobiological mechanisms underlying cognitive impairment in PD.